PENGGUNAAN MEDIA PUZZLE MELALUI BIMBINGAN KELOMPOK UNTUK MENGATASI KEJENUHAN BELAJAR SISWA DI SMP NEGERI 1 BAITUSSALAM - Andini Nur Hanani; Wanty Khaira (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effectiveness of using crossword puzzle media through group guidance services in overcoming learning burnout among students at SMP Negeri 1 Baitussalam. The research utilizes a quantitative approach with a one-group pretest–posttest experimental design. The research subjects consisted of 6 students who had high levels of learning burnout based on pretest results. The media used in this study is a crossword puzzle developed by the researcher and has undergone a judgment process by media experts. The research instrument is a learning burnout questionnaire that has been tested for validity and reliability. Data collection was carried out through a pretest, the implementation of treatment across three sessions using puzzle media within group guidance services, and a posttest. Data analysis utilized the Shapiro–Wilk normality test and the Paired Sample t-test hypothesis test with the assistance of SPSS version 26. The results showed a decrease in students' learning burnout levels after the treatment, with a significance value (Sig. 2-tailed) of 0.000 < 0.05. Thus, the use of crossword puzzle media through group guidance services is effective in overcoming student learning burnout